Longitudinal changes in location-specific cartilage thickness and T2 relaxation-times after posterior cruciate ligament reconstruction for isolated and multiligament injury. (October 2020) - Culvenor, Adam G.; Wirth, Wolfgang; Boeth, Heide; Duda, Georg N.; Eckstein, Felix
Abstract: Background: Knee cartilage undergoes pathological changes after anterior cruciate ligament rupture. However, little is known about the development and progression of structural pathology after posterior cruciate ligament (PCL) injury. This study aimed to determine the location-specific longitudinal changes in knee cartilage morphology (thickness) and composition (T2 relaxation-times) after PCL rupture and reconstruction (PCLR) and compare these to uninjured controls. Methods: Fifteen adults (mean age 39 years (standard deviation 10), 12 men) with PCLR for isolated and multiligment injury had MRIs acquired at a minimum 5 years post-PCLR and 1 year later. Location-specific changes in knee cartilage thickness and T2 relaxation-times were determined quantitatively after segmentation, and compared with annualised cartilage changes in 13 active controls (mean age 45 years (standard deviation 4), 6 men). Findings: Following PCLR, the annual loss of cartilage thickness was greatest in the medial femoral condyle (mean −4.0%, 95% confidence interval [95% CI] −6.7, −1.4), medial tibia (mean −3.7%, 95% CI −6.1, −1.3), and patella (mean −3.2%, 95% CI −4.7, −1.6). In the medial femoral condyle and trochlea, the PCLR group lost significantly more cartilage thickness than uninjured controls (mean difference −3.7%, 95% CI −0.9, −6.5; and −1.8%, 95% CI −0.1, −3.6, respectively). Deep and superficial zone T2 relaxation-times were relatively constant over time, without longitudinal differences between PCLR and control knees. Interpretation: PCL reconstructed knees displayed substantially greater rates of cartilage loss in the medial tibiofemoral and patellofemoral compartments compared to uninjured controls, highlighting that the process of degeneration remains active many years after injury. Highlights: First longitudinal study of cartilage thickness/composition following PCL injury PCL injured knees rapidly lose medial tibiofemoral and patellofemoral cartilage. Cartilage loss was not associated with thigh muscle size or body mass index. PCL injury is an attractive model for evaluating disease modifying interventions.